Modeling and Experimental Verification of Ultrasound Transmission in Electro Insulation Oil - WOTZKA, Daria; CICHOŃ, Andrzej; BOCZAR, Tomasz (Archives of Acoustics, 2012)
A verification study of ultrasound transmission numerical simulation results with experiment resultsis presented in this paper. The work considers a model of a transformer tank which is filled with electroinsulating oil. In the experiment, performed under laboratory conditions, an ultrasound wave is generatedby a piezoelectric transducer that is fixed in the centre of the tank and measured by another transducermounted inside the tank at three distances: 10, 20 and 30 cm from the sound source. The transducer is ableto measure and generate acoustic waves in the ultrasound frequency band up to 1 MHz. The simulationconsiders numerical calculation of acoustic pressure distribution inside the tank in which acoustic sourceemits waves with frequency equal to 100 kHz. Verification analysis has confirmed consistency of thenumerically calculated values with the measurement results.